Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the simultaneous equations:
[tex]\[ \begin{array}{c} e + d + \frac{1}{f} = 0 \\ 2e - d + \frac{3}{f} = -9 \\ 3e + 2d - \frac{4}{f} = 19 \end{array} \][/tex]
We need to find the values of [tex]\( e \)[/tex], [tex]\( d \)[/tex], and [tex]\( f \)[/tex] that satisfy all three equations.
### Step-by-Step Solution:
1. Express [tex]\( \frac{1}{f} \)[/tex] in terms of [tex]\( e \)[/tex] and [tex]\( d \)[/tex] from the first equation:
[tex]\[ e + d + \frac{1}{f} = 0 \implies \frac{1}{f} = -e - d \quad \text{(Equation 1.1)} \][/tex]
2. Substitute [tex]\( \frac{1}{f} \)[/tex] from Equation 1.1 into the second equation:
[tex]\[ 2e - d + \frac{3}{f} = -9 \\ 2e - d + 3(-e - d) = -9 \\ 2e - d - 3e - 3d = -9 \\ -e - 4d = -9 \quad \Rightarrow \quad e + 4d = 9 \quad \text{(Equation 2.1)} \][/tex]
3. Substitute [tex]\( \frac{1}{f} \)[/tex] from Equation 1.1 into the third equation:
[tex]\[ 3e + 2d - \frac{4}{f} = 19 \\ 3e + 2d - 4(-e - d) = 19 \\ 3e + 2d + 4e + 4d = 19 \\ 7e + 6d = 19 \quad \text{(Equation 3.1)} \][/tex]
4. We now have a system of two equations with two variables:
[tex]\[ \begin{cases} e + 4d = 9 \quad \text{(Equation 2.1)} \\ 7e + 6d = 19 \quad \text{(Equation 3.1)} \end{cases} \][/tex]
5. Solve this system of linear equations. First, we solve Equation 2.1 for [tex]\( e \)[/tex]:
[tex]\[ e = 9 - 4d \quad \text{(Equation 2.2)} \][/tex]
6. Substitute Equation 2.2 into Equation 3.1:
[tex]\[ 7(9 - 4d) + 6d = 19 \\ 63 - 28d + 6d = 19 \\ 63 - 22d = 19 \\ -22d = 19 - 63 \\ -22d = -44 \\ d = 2 \][/tex]
7. Substitute [tex]\( d = 2 \)[/tex] back into Equation 2.2 to find [tex]\( e \)[/tex]:
[tex]\[ e = 9 - 4(2) \\ e = 9 - 8 \\ e = 1 \][/tex]
8. Find [tex]\( f \)[/tex] using Equation 1.1:
[tex]\[ \frac{1}{f} = -e - d = -1 - 2 = -3 \\ f = -\frac{1}{3} \][/tex]
### Final Solution:
The values that satisfy all three equations are:
[tex]\[ e = 1, \quad d = 2, \quad f = -\frac{1}{3} \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ \boxed{(1, 2, -\frac{1}{3})} \][/tex]
[tex]\[ \begin{array}{c} e + d + \frac{1}{f} = 0 \\ 2e - d + \frac{3}{f} = -9 \\ 3e + 2d - \frac{4}{f} = 19 \end{array} \][/tex]
We need to find the values of [tex]\( e \)[/tex], [tex]\( d \)[/tex], and [tex]\( f \)[/tex] that satisfy all three equations.
### Step-by-Step Solution:
1. Express [tex]\( \frac{1}{f} \)[/tex] in terms of [tex]\( e \)[/tex] and [tex]\( d \)[/tex] from the first equation:
[tex]\[ e + d + \frac{1}{f} = 0 \implies \frac{1}{f} = -e - d \quad \text{(Equation 1.1)} \][/tex]
2. Substitute [tex]\( \frac{1}{f} \)[/tex] from Equation 1.1 into the second equation:
[tex]\[ 2e - d + \frac{3}{f} = -9 \\ 2e - d + 3(-e - d) = -9 \\ 2e - d - 3e - 3d = -9 \\ -e - 4d = -9 \quad \Rightarrow \quad e + 4d = 9 \quad \text{(Equation 2.1)} \][/tex]
3. Substitute [tex]\( \frac{1}{f} \)[/tex] from Equation 1.1 into the third equation:
[tex]\[ 3e + 2d - \frac{4}{f} = 19 \\ 3e + 2d - 4(-e - d) = 19 \\ 3e + 2d + 4e + 4d = 19 \\ 7e + 6d = 19 \quad \text{(Equation 3.1)} \][/tex]
4. We now have a system of two equations with two variables:
[tex]\[ \begin{cases} e + 4d = 9 \quad \text{(Equation 2.1)} \\ 7e + 6d = 19 \quad \text{(Equation 3.1)} \end{cases} \][/tex]
5. Solve this system of linear equations. First, we solve Equation 2.1 for [tex]\( e \)[/tex]:
[tex]\[ e = 9 - 4d \quad \text{(Equation 2.2)} \][/tex]
6. Substitute Equation 2.2 into Equation 3.1:
[tex]\[ 7(9 - 4d) + 6d = 19 \\ 63 - 28d + 6d = 19 \\ 63 - 22d = 19 \\ -22d = 19 - 63 \\ -22d = -44 \\ d = 2 \][/tex]
7. Substitute [tex]\( d = 2 \)[/tex] back into Equation 2.2 to find [tex]\( e \)[/tex]:
[tex]\[ e = 9 - 4(2) \\ e = 9 - 8 \\ e = 1 \][/tex]
8. Find [tex]\( f \)[/tex] using Equation 1.1:
[tex]\[ \frac{1}{f} = -e - d = -1 - 2 = -3 \\ f = -\frac{1}{3} \][/tex]
### Final Solution:
The values that satisfy all three equations are:
[tex]\[ e = 1, \quad d = 2, \quad f = -\frac{1}{3} \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ \boxed{(1, 2, -\frac{1}{3})} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.